Análisis espacial de calidad atmosférica de pm 10, pm 2,5 ruido y vibración generados por la actividad minera no metálica de la empresa Ecuapet S.C.C., ubicada en la parroquia Mulaló, periodo 2022. - Chimba Almachi, Pedro Andrés (2022)
The objective of this research was to evaluate the atmospheric quality in the non-metallic mining company “Ecuapet S.C.C.” through a spatial analysis of critical points of affectation. For which, monitoring was carried out, establishing methodologies for the concentration determination of particulate material PM10, PM2.5; sound pressure level from the specific noise and residual noise with the dB, dBA, and dBC measurement filters, in terms of ground vibration, acceleration, displacement, and speed were measured. The quantitative method was used to determine the concentrations of particulate matter in the air, residual/specific noise and vibration, using the data obtained by the method in question to find the points with the highest concentrations. Getting results in terms of PM10, a maximum concentration of 97.83 ug/m3, and PM2.5, the highest value of 49.67 ug/m3, does not exceed the maximum permissible limits. According to the calculation of the corrected equivalent continuous noise index, the points where it exceeds the maximum possible limit are the loading area with a maximum value of 82.49 dB and the land removal area with the highest value of 79.5 dB; associated with the generation of noise is the vibration generated by the front loader, caterpillar-type tractor, and cargo vehicles; however, on the outskirts of the mine, the noise levels are extremely low with a minimum record of 45.32 dB, this is a consequence of the functionality of the ecological barrier. The impact that is generated at the place of influence in the social aspect, causes discomfort due to the influx of cargo vehicles to the mine as well as in the environmental part, the change in the natural conditions of the place influencing the alteration of soil structure. Finally, it was concluded that there was no contamination that exceeded the maximum permissible limits for particulate matter, but with regard to noise, there was evidence of contamination above the limits established in Ecuadorian environmental regulations.